Multiple/Two‐Way Shape Memory Poly(urethane‐urea‐amide) Elastomers. Issue 3 (7th February 2023) - Li, Zhen; Mei, Shuxiang; Luo, Lu; Li, Siyuan; Chen, Xiaoyin; Zhang, Yuancheng; Zhao, Wei; Zhang, Xiaomeng; Shi, Ge; He, Yanjie; Cui, Zhe; Fu, Peng; et al.
Abstract : Front Cover : Article 2200693 by Yuancheng Zhang, Peng Fu and co‐workers reveals that a semi‐crystalline block poly(urethane‐urea‐amide) elastomers (PUUAs), which are prepared by the copolymerization of isocyanateterminated polyurethane and amino‐terminated polyamide‐1212, present multiple, reversible two‐way and high temperature shape memory effect and have a potential for more complex and changeable applications, such as high temperature sensors, actuators, aerospace equipment, etc.